Theoretical description of sotolone electrochemical determination in wine in basic media over an undoped conducting polymer - Tkach, Volodymyr; Kushnir, Marta; Kopiika, Vira; Luganska, Olga; Omelyanchyk, Lyudmyla; Kormosh, Zholt; Kucher, Mykhailo; Garcia, Jarem; Palamarek, Karina; Bagrii, Konon; Medvedeva, Anzhelika; Oliveira, Sílvio C.; et al. (My University, 2023)
The electrochemical determination of sotolone in basic media over an undoped conducting polymer has been described for the first time. The alkaline hydrolysis, breaking the furanonic ring, leads to the appearance of an acid ion, entering the polymer matrix as a dopant. The stability analysis of the system, made by the development and investigation of the correspondent mathematical model, shows that the sotolon electrochemical determination is made efficiently. As for the oscillatory behavior, it may also be caused by the cyclic effect of chemical and electrochemical stages on the double electric layer capacitance and impedance.

Вперше описано електрохімічне визначення сотолону в основних середовищах над нелегованим провідним полімером. Лужний гідроліз, розриваючи фуранове кільце, призводить до появи кислотного іона, що входить до полімерної матриці як допант. Аналіз стійкості системи, проведений розробкою та дослідженням відповідної математичної моделі, показує, що сотолонне електрохімічне визначення проводиться ефективно. Що стосується коливальної поведінки, вона також може бути викликана циклічним впливом хімічних і електрохімічних етапів на ємність і імпеданс подвійного електричного шару.
Keywords: кафедра біотехнології продуктів бродіння і виноробства; sotolone; conducting polymers; electrochemical sensors; oscillatory behavior; stable steady-state; сотолон; провідні полімери; електрохімічні датчики; коливальна поведінка; стабільний стаціонарний стан